2014
DOI: 10.3324/haematol.2013.095257
|View full text |Cite
|
Sign up to set email alerts
|

The reliability of immunohistochemical analysis of the tumor microenvironment in follicular lymphoma: a validation study from the Lunenburg Lymphoma Biomarker Consortium

Abstract: The cellular microenvironment in follicular lymphoma is of biological and clinical importance. Studies on the clinical significance of non-malignant cell populations have generated conflicting results, which may partly be influenced by poor reproducibility in immunohistochemical marker quantification. In this study, the reproducibility of manual scoring and automated microscopy based on a tissue microarray of 25 follicular lymphomas as compared to flow cytometry is evaluated. The agreement between manual scori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 43 publications
(52 reference statements)
1
54
0
2
Order By: Relevance
“…15 This study, conducted by highly experienced hematopathologists, found only low to moderate agreement in manual scoring of T cells and macrophage markers when four to five scoring categories were used. However, comparison of automated analyses set up by two different operators in two different instruments using the same methodology was highly reproducible for T-cell markers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 This study, conducted by highly experienced hematopathologists, found only low to moderate agreement in manual scoring of T cells and macrophage markers when four to five scoring categories were used. However, comparison of automated analyses set up by two different operators in two different instruments using the same methodology was highly reproducible for T-cell markers.…”
Section: Discussionmentioning
confidence: 99%
“…Large and interdigitating cells, such as macrophages, are difficult to quantify. 15 The image analysis training was challenging and focused on capturing the areas of dark brown IHC staining present in the cell bodies. CD68 staining was heterogeneous in this cohort.…”
Section: Heterogeneous Density Of Immune Cells In the Microenvironmenmentioning
confidence: 99%
“…Previous IHC-based validation studies of microenvironment cell populations by the Lunenburg Lymphoma Biomarker Consortium (LLBC), in both diffuse large B-cell Lymphoma (DLBCL) and FL, have highlighted the poor reproducibility of manual scoring even by experienced pathologists, and advocated computer-assisted scoring as being the more reliable technique. 26,27 Recently, the mutational spectrum of FL tumor cells and their prognostic value have been reported. [28][29][30] Most notably, Pastore et al demonstrated the value of combining mutation status with clinical FLIPI and performance status to improve upon the prognostic value of FLIPI alone (45-55%) to 64-72% for M7-FLIPI, with a comparable negative prognostic value.…”
Section: Introductionmentioning
confidence: 99%
“…A validation study from a lymphoma consortium on the FL microenvironment reported considerable differences between manual scoring and automated microscopy systems and flow cytometry, which was also dependent on the investigating laboratory. 74 Within semi-automated image analysis systems, a high concordance seems to exist. 49 Among the included studies, expression was predominantly assessed by IHC.…”
Section: Discussionmentioning
confidence: 99%